Temporal Evolution of a Network Jet’s Physical Properties Inferred from FISS/GST and IRIS Observations - Eun-Kyung Lim; Jongchul Chae; Kyuhyoun Cho; Vasyl Yurchyshyn; Heesu Yang; Kyung-Suk Cho; Hannah Kwak; Donguk Song; Maria S. Madjarska (The Astrophysical Journal)
Small-scale jets, such as chromospheric and transition region (TR) network jets, are of great interest regarding coronal heating and solar wind acceleration. Spectroscopic analysis based on multiple spectral lines with different formation temperatures is essential for understanding the physical properties and driving mechanisms of jets. Here, we conduct an investigation of the physical properties of a small-scale chromospheric jet in a quiet-Sun network region and its TR counterpart. This jet is recorded from formation to extinction using the Fast Imaging Solar Spectrograph at the Goode Solar Telescope and the Interface Region Imaging Spectrograph. The chromospheric component of the jet exhibits a high line-of-sight speed of up to 45 km s ^−1 during its ascending phase, accompanied by spectral profiles akin to rapid blueshifted excursion and downflowing rapid redshifted excursion during the descending phase. Using a cloud model combined with a Multi-Layer Spectral Inversion, we quantify the jet’s temperature during its ascending phase, which starts at approximately 11,000 K and increases by only 1000 K over 1 minute, much smaller than a few 10 ^4 K, the excess temperature expected in an ideal gas reconnection jet at an outflow speed of 45 km s ^−1 . The TR counterpart exhibits a Si iv 1394 Å line profile with a non-Gaussian shape, including a blueshifted component and a large nonthermal width. Our results suggest that if the jet is driven by magnetic reconnection in the chromosphere, the heat released by the reconnection may be mostly used to ionize the hydrogen rather than to increase the temperature so that the gas may appear almost isothermal.